IMPLEMENTASI TELENURSING PADA PASIEN DIABETES MELITUS: INTEGRATIVE LITERATURE REVIEW - Ratna Wirawati Rosyida; Febriana Sartika Sari; Duwi Pudji Astuti (PROFESSIONAL HEALTH JOURNAL, 2023)
Introduction: Telenursing is the effective strategic in nursing intervention. It gives benefits in many chronic cares, especially in diabetes mellitus. This study aimed to gather evidences about application of telenursing and its benefits for DM patients. Methods: integrative literature review was conducted in this study. PRISMA flowchart used as guidance in literature searching. Online databases were Pubmed, ProQuest, EbscoHost, and Sciencedirect. Inclusion and exclusion criteria were determined in gaining the related literature..Summarizing the literature was showed in the table. Results: Total of 7 articles were selected in this study. Five articles were from developing country, one article as from developed country, and the other was not stated clearly. Five articles also used RCT design, one article used quasy experiment, and remain article used longitudinal mixed method case study design Conclusion: there are several telenursing-based intervention applied in clinical setting. Telenursing-based intervention used some modalities including telephone or video conference in giving the education for patients with diabetes mellitus